Crianças no pátio escolar :a utilização dos espaços e o comportamento infantil no recreio - Fernandes, Odara de Sá (2006)
The interest for understanding the relationship of the child with its environment has increased in the whole world during the last few years. Several researchers, using Environmental Psychology as basis, have analyzed the implications of this relation for the child development and the organization of playful spaces. Being a place where children spend a great part of their time and develop many intellectual and social abilities, the school becomes one of the main focus of this research. This study investigated different sectors of the outdoor area of NEI -UFRN, during the recreation time, in which the use of space and the interaction between children were analyzed, through the observation of the child behavior (place-centered and individual-centered mapping). The results had disclosed that the school s outdoor area and its equipments presents a great range of choices possible to the children, however its occupation is not uniform: there are areas very used and others almost without use. Generally, this heterogeneity happens again in relation to the distribution of the interaction states in the sectors, the friendly associative behavior being the most present. The observation of children behaviors favored a better understanding of the use of the spaces, and contributed for discussion about the environment what these users really need for a healthy development, including differences in related to gender, age and daytime. In spite of the studied outdoor areas being vast, pleasant and varied, it needs a better distribution of its equipments and a plan that allows greater children participation in the place organization